2020
DOI: 10.1155/2020/9316763
|View full text |Cite
|
Sign up to set email alerts
|

Secretory IgA in Mucosa of Pharynx and Larynx Plays an Important Role against Influenza A Virus Infection in Kidney Yang Deficiency Syndrome Model

Abstract: Objective. Influenza virus poses a major threat to human health and has serious morbidity and mortality which commonly occurs in high-risk populations. Pharynx and larynx of the upper respiratory tract mucosa is the first defense line against influenza virus infection. However, the ability of the pharynx and larynx organ to eliminate the influenza pathogen is still not clear under different host conditions. Methods. In this study, a mouse model of kidney yang deficiency syndrome (KYDS) was used to mimic high-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Regarding the SIgA levels, it was reported that these antibodies present in the mucosa are closely associated with the severity of viral infection and the reduction of these levels can compromise severely the local immune response ( 13 ). So, the observation that COVID-19 patients with ARDS presented higher SIgA levels can reinforce the previous literature concerning other respiratory virus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the SIgA levels, it was reported that these antibodies present in the mucosa are closely associated with the severity of viral infection and the reduction of these levels can compromise severely the local immune response ( 13 ). So, the observation that COVID-19 patients with ARDS presented higher SIgA levels can reinforce the previous literature concerning other respiratory virus.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, reduced airways mucosal SIgA levels leads to an increased risk of developing upper respiratory tract infections (URTI) ( 11 ), mainly by respiratory virus ( 12 ). It is also of utmost highlight that decreased SIgA levels are closely related to the illness severity ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy to mention that a reduction in the airways mucosal SIgA levels is associated with a higher risk of upper respiratory tract infection (URTI) development [39] mainly by a respiratory virus [41], such as rhinovirus, respiratory syncytial virus, and influenza virus [42]. In addition, it was reported that lower SIgA levels are associated with illness severity [43].…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, the production and release of cytokines by the upper airway’s mucosa, in response to respiratory infection, can elicit different immune response profiles such as Th1, Th2, and Th17, which can help in the production of mucosal specific-SIgA against the infective agent ( 10 ). Among some SIgA features, it is paramount to point out that it was reported that reduction in SIgA levels is closely associated with illness severity ( 13 ). Secretory immunoglobulin A is considered as the “first line of defense” against many different pathogens due to its capacity to directly bind and inhibit many pathogenic agents in the mucosa ( 14 – 16 ).…”
Section: Introductionmentioning
confidence: 99%